ANALISIS PERSEPSI PENERAPAN MODEL ORGANISASI PEMBELAJARAN DI PTN “X” - Sri Bawono; Sjafri Mangkuprawira; Heny K. Daryanto2; Ma’mun Sarma (Bina Nusantara University, 2010)
PTN “X” as a higher educational organization, has developed its capacity to grow and learn into a world-class university. Learning Organization by Senge (1995) is an organization that continually expand their capacity to create the future with innovation strategy, namely to change ideas (ideas) into something useful for the organization and its environment, by engaging individuals and teams that exist. There are five disciplines as the concept of learning organization: personal mastery, mental model, shared vision , team learning and system thinking.Nowadays, PTN “X” has applied an organizational learning and it came up into several unpleasant results. The main problems were mainly due to deficiencies and constraints in human resources. There are no clear guidelines on the internal organization of PTN “X”. This research is correspondingly made in pursuing objectives to analyze the perceptions of respondents regarding the application of organizational learning in the PTN “X”. There are four principles that has not been fully executed, mental models, system thinking, shared vision and team learning while, personal mastery rated well.